Soil Physicochemical and Metagenomic Analyses of Bacteria and Fungi: Toward Desert Truffle Cultivation in Saudi Arabia - Sakhr Alhuthali; Suleiman K. Bello; Ahmed M. Bageel; Amal Bakr Shori; Noor M. Bataweel; Ahmed M. Al-Hejin; Abdulaziz A. Al-Qarawi; Paul W. Thomas (Agronomy)
Researchers are exploring plant-based protein sources to address both malnutrition and climate change. Desert truffles are rich in protein (i.e., <semantics>≈</semantics>20%) and offer a cheaper and more environmentally friendly option. However, desert truffle cultivation is limited by environmental factors like rainfall and soil properties. This study was conducted to understand the soil conditions and microbiomes associated with desert truffles growing in parts of Saudi Arabia. Based on yield, the truffle fields were categorized into high-yield (<semantics>≈</semantics>50 kg/ha annually) and low-yield (<semantics>≈</semantics>2 kg/ha annually) truffle farms. Truffle yield differences were not significantly influenced by most soil physicochemical variables except for total nitrogen (negatively correlated). However, low soil nitrogen alone did not explain yield disparities, as wild truffle fields with low nitrogen also produced fewer truffles. In contrast, truffle yield showed a strong positive correlation with calcium carbonate content. We hypothesized that the unmeasured irrigation schedule was most likely behind the truffle yield differences especially during fruiting season. Furthermore, the high-yield farms had lower bacteria richness and diversity than the low-yield farms. Environmentally important bacteria genera such as Geodermatophilus and Rubrobacter were found in both farms, although more were found in the low-yield one, whereas more Streptomyces were found in the high-yield farm. In addition, fungal alpha diversity was higher in the high-yield farm with the dominance of Sordariomycetes, Dothideomycetes, Eurotiomycetes, and Glomeromycetes.